Traditional game based on e-learning method to improve the basic locomotor movements - Wijaya, Ridho Gata; Fitri, Ebtana Sella Mayang (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2023)
Physical education and sports in elementary schools have a central role in the growth and development of students in preparing themselves to face the future. One of the tasks and functions of physical education is to develop the quality and quantity of students' basic movements. This can be developed through traditional game-based learning methods. This research aimed to produce basic locomotor movements through a traditional game-based learning model for students at the elementary school level and to determine the feasibility and practicality of the game model developed to improve basic locomotor movements and cooperation for lower grade elementary school students. This research used the research and development model based on Traditional Games. The research subjects were teachers and students at the elementary school level. The data collection instruments used were observations, interviews and questionnaires. The data analysis techniques used are quantitative and qualitative analysis. The results of the validity and reliability tests showed that the simple game-based PJOK learning model developed was valid and reliable, so that the product is suitable for use in the learning model. Based on the results of teacher and student assessments, it shows that the simple game-based PJOK learning model which was developed to improve locomotor movement and overall cooperation is stated to be very good. It can be concluded that this is a game model that can be used to develop locomotor movement and cooperation skills for elementary school level students.